Sitem Pendukung Keputusan Penentuan Jurusan Pada Tingkat SMK Menggunakan Metode SMART (Studi Kasus:SMK Negeri2 Binjai) - Elisa Putri Sembiring (Journal of Information and Technology, 2021)
Programs at the high school level makes it difficult students make choicesthatsuitcapabilities.Someofthefactorsthatinfluencesuchamistakeinchoosing majors went along with friends or majors trends of today and parentreferences, so that they appear remorse for students who have determined thechoice if it is not in accordance with their interests, abilities or talents. Thereforeit takes a decision support system that can perform the calculation criteria of thestudentstohelpdetermineappropriateschooldepartment.Thissystemimplements the SMART method based on the criteria of each alternative, namelytheIndonesiaNationalexamscores,theEnglishNationalexamscores,theMathematics National exam scores, the Natural SciencesNational exam scores.The result of this system is the value of knowledge for determining the directionbased on predetermined criteria. Of the 10 alternative or candidate is taken, thereis4eligible student majoring in technical light vehicle,4 eligible student majoringin bodyrepairtechniques and 2 eligiblestudentmajoring in welding technique.